MEDIA TRANSFORMATION OF ALTERNATE UNIVERSE (AU) USING K-POP ARTISTS' VISUAL CLAIMS INTO NOVEL FORM - Wiratsih, Woro; Wahyuni, Aprilia Kristiana Tri (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2024)
Alternate Universe (AU) is a form of popular fiction that is much loved by today's young generation. In the AU form found on social media, the storyline is built not with narrative but with pictures containing chats between characters and also photos with visual claims of K-Pop idols. The tendency of the younger generation who are also K-Pop fans is currently to prefer reading AU in the form of fanfiction which presents light plots and conflicts with visual claims using more interesting K-Pop group idols. However, in its development, a debate emerged that the AU could not be considered a work of fiction because it did not have narratives that build a storyline from the conflict raised like a literary work such as a novel. This research uses a virtual ethnographic method where researchers conducted interviews with 7 AU writers to find out the process of transferring media from fictional stories from pictures containing conversations to short messages or uploading stories on social media with visual claims using the faces of K-Pop idols into works. fiction in the form of a novel. This data was used to determine the obstacles in creating narratives in novels based on their AU works. Apart from that, direct observations were also carried out by comparing AU works and novels from the author's titles to find out how descriptions were developed in narrative form and sentence formation in paragraphs in the novel. This research aims to explain the process of converting AU's work into a complete novel. From these interviews and comparing the AU form with the novel form, it was found that there was a change in the storyline, especially in the development of conflict because AU works were felt to be lighter and often the conflict was not strong enough to be written in a work of fiction in the form of a novel. Apart from that, there are also several novels that still include pictures containing typical AU short messages in the novel because they feel that these scenes are difficult to turn into narratives. There were many parts that ended up being replaced and changed to create a complete novel. Keywords: Alternate universe, novel, media transformation AU to novel, narration, visual claim.